Pengaruh Atribut Produk Wisata dan Citra Destinasi Terhadap Keputusan Berkunjung Pada Destinasi Wisata Taman Sri Baduga Kabupaten Purwakarta - Aulia Rafika; Edi Suswardji Nugroho (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to determine the effect of tourism product attributes and destination image, either directly, indirectly, partially and simultaneously on the decision to visit the Taman Sri Baduga Kabupaten Purwakarta tourist destination, and the results of this study can be useful for Stake Holders in the field of tourism and can contribute for science.The paradigm of this research is a quantitative descriptive verification paradigm with a focus on testing theory through measuring research variables using the statistical technique / SPSS 24 approach, data collection using the incidental sampling technique on 398 respondents with research subjects who are visitors or who have visited Taman Sri Baduga Purwakarta tourist destinations. Before testing the hypothesis, this study conducted a data validity test. Data analysis technique used is the scale range analysis technique and path analysis.There is a significant effect of the partial attributes of tourism products on the decision to visit by 55.3% and the partial effect of the image of the destination on the decision to visit by 28%. Then there is a simultaneous influence of tourism product attributes and destination image on the decision to visit Taman Sri Baduga Purwakarta of 83.3%, the remaining 16.7% is influenced by other factors not included in this study. Keywords: Tourism Product Attributes, Destination Image, and Decision to Visit